Instagram filter with AR technology as an innovation for introducing fauna to Generation Z in Indonesia - Albani, Salmaan Daffa; Rachman, Anung; Panindias, Asmoro Nurhadi (Universitas Negeri Yogyakarta, 2024)
Fauna preservation is a crucial undertaking necessary for sustaining the survival of animal species globally. However, the issue of wildlife conservation often lacks widespread recognition, particularly among individuals aged between 13 and 28 years old, commonly referred to as Generation Z. To address this gap, the author proposes a solution utilizing Augmented Reality (AR) technology through Instagram filters to introduce fauna to the Generation Z demographic in Indonesia. Employing the Double Diamond method, consisting of four key stages (Discover, Define, Develop, and Deliver), the author aims to develop an effective solution for fauna preservation in Indonesia. The research findings indicate that Instagram filters incorporating AR technology significantly enhance the public's understanding of fauna in Indonesia. Furthermore, these filters successfully capture the attention of the public, particularly the younger generation, known for their preference for engaging and captivating content. Consequently, Instagram filters leveraging AR technology emerged as an innovative solution for fauna preservation in Indonesia.